Perancangan Sistem Informasi Pemesanan Tiket Kereta Api (PERSERO) Palembang Menggunakan Java Netbeans - Muhammad Yoga Wahyu Nugraha; Muhammad Ihsan; Meilyana Winda Perdana (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
In a train ticket booking also has an obstacle, to overcome the obstacles found in conventional ticket booking such as piling up queues at the station, limited time owned by consumers, the process of delivering information about ticket prices for the day of departure or the previous date that cannot be processed, then PT Kereta Api (Persero) Palembang provides solutions through applications that will be made to facilitate ticket booking, Fast transaction process, delivery of information about schedules and ticket prices that can be accessed quickly. In designing this system using a method, namely the Prototype method.